Single-cell profiling aligns CD56bright and cytomegalovirus-induced adaptive natural killer cells to a naïve-memory relationship - Panjwani, M. Kazim; Grassmann, Simon; Sottile, Rosa; Le Luduec, Jean-Benoît; Kontopoulos, Theodota; van der Ploeg, Kattria; Sun, Joseph C.; Hsu, Katharine C. (Frontiers in Immunology, 2024)
Development of antigen-specific memory upon pathogen exposure is a hallmark of the adaptive immune system. While natural killer (NK) cells are considered part of the innate immune system, humans exposed to the chronic viral pathogen cytomegalovirus (CMV) often possess a distinct NK cell population lacking in individuals who have not been exposed, termed “adaptive” NK cells. To identify the “naïve” population from which this “memory” population derives, we performed phenotypic, transcriptional, and functional profiling of NK cell subsets. We identified immature precursors to the Adaptive NK cells that are equally present in both CMV+ and CMV- individuals, resolved an Adaptive transcriptional state distinct from most mature NK cells and sharing a common gene program with the immature CD56bright population, and demonstrated retention of proliferative capacity and acquisition of superior IFNγ production in the Adaptive population. Furthermore, we distinguish the CD56bright and Adaptive NK populations by expression of the transcription factor CXXC5, positioning these memory NK cells at the inflection point between innate and adaptive lymphocytes.